Culture of masculinity, alcohol consumption and risk to cancer: an international survey (Research, Society and Development, 2023)
Objective: To understand the underlying cultural effects of masculinity on alcohol consumption and the associated risk for cancer. Method: An exploratory online survey. Data was collected (2018-2019) from 176 men living in 9 countries who responded to an online survey in English, French, Italian, Portuguese, or Spanish. Socio-demographic data and responses to close-ended questions were compiled as descriptive statistics. Responses to the open-ended questions were analyzed using thematic analysis with the pre-established themes: alcohol consumption and its acceptance for men in respondents’ ethno-cultural groups; and thoughts about scientific evidence concerning the consumption of alcohol in high concentration and heightened risk of cancer. Results: Most respondents were under 30 years of age (33.7%). Results across the linguistic sub-samples indicate that among 10 statements, alcohol consumption is part of most students’ life (18.8%), it facilitates acceptance in social groups (16.9%), and it is not repressed at social gatherings (16.6%). Construction (27.5%) was the top among professions in which alcohol consumption is most common. Among situational factors related to alcohol consumption, respondents chose stress (18.1%), unemployment or unstable job (18.0%), and financial trouble (17.9%). Perceptions of acceptance of alcohol consumption are influenced by traditional masculinity-related values, beliefs, and behaviors and the acknowledged lack of cancer literacy were revealed as conditions promoting a risk for cancer. Conclusion- Alcohol consumption is normalized to a certain extent among men of different ages and backgrounds. Evidence informs policymakers and health promoters as they develop legislation and programming to limit unhealthy behavior related to alcohol consumption.